Audio Visual Media Components in Educational Game for Elementary Students - Meilani Hartono; Andri Guna Santoso; Crisantus Lebu Raya; Budi Yulianto; Suwarno Suwarno (ComTech: Computer, Mathematics and Engineering Applications, 2016)
The purpose of this research was to review and implement interactive audio visual media used in an educational game to improve elementary students’ interest in learning mathematics. The game was developed for desktop platform. The art of the game was set as 2D cartoon art with animation and audio in order to make students more interest. There were four mini games developed based on the researches on mathematics study. Development method used was Multimedia Development Life Cycle (MDLC) that consists of requirement, design, development, testing, and implementation phase. Data collection methods used are questionnaire, literature study, and interview. The conclusion is elementary students interest with educational game that has fun and active (moving) objects, with fast tempo of music, and carefree color like blue. This educational game is hoped to be an alternative teaching tool combined with conventional teaching method.